2016
DOI: 10.1007/s12206-016-0522-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel design procedure for tractor clutch fingers by using optimization and response surface methods

Abstract: This paper presents a methodology for re-designing a failed tractor transmission component subjected to cyclic loading. Unlike other vehicles, tractors cope with tough working conditions. Thus, it is necessary to re-design components by using modern optimization techniques. To extend their service life, we present a design methodology for a failed tractor clutch power take-off finger. The finger was completely re-designed using topology and shape optimization approach. Stress-life based fatigue analyses were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…The clutch is the main part of a tractor's powertrain, located between the engine and the transmission, which serves to transfer or disconnect the engine's power to the transmission [39].…”
Section: Clutch Actuatormentioning
confidence: 99%
“…The clutch is the main part of a tractor's powertrain, located between the engine and the transmission, which serves to transfer or disconnect the engine's power to the transmission [39].…”
Section: Clutch Actuatormentioning
confidence: 99%
“…Topoloji optimizasyonu birçok yapısal problemin boyutsal iyileştirmenin yapıldığı bir yöntem olarak karşımıza çıkmaktadır. Literatürde çok farklı elemanların topoloji optimizasyonu ile boyutsal olarak iyileştirildiği görülmektedir [7][8]. Ancak bu yöntemde elde edilen malzeme dağılımları bazı durumlarda geleneksel yöntemlerle üretilemeyecek kadar karmaşık yapıda olduğu görülmektedir.…”
Section: Introductionunclassified
“…The cost of the power transmission components of a tractor is approximately 25-30% of its total cost [1]. A cost reduction to be realized return to companies as profitability in mass production.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed a method to find optimum PTO finger design in order to maximize fatigue life while minimizing the von -Mises stress, deformation, and the mass. As a result, a stiffer and lightweight design of the PTO finger was obtained by comparing a PTO finger used in the market [1]. Karpat et al overdesigned a chain link to optimize stress and mass values.…”
Section: Introductionmentioning
confidence: 99%